Case report: Fatal systemic embolism caused by early prosthetic valve endocarditis after Bentall surgery - Wu, Shaofeng; Wang, Xin; Ren, Weidong; Song, Guang; Hou, Yang; Hu, Haidi; Yu, Xiaona (Frontiers in Cardiovascular Medicine, 2023)
Prosthetic valve endocarditis (PVE) is a rare but dangerous complication of Bentall surgery and Staphylococcus epidermidis PVE involving multiple valves simultaneously during the early postoperative period has not been reported. A 42 year old patient admitted to intensive care unit with fever one month after aortic valve replacement (Bentall procedure). Echocardiography was of great diagnosis value and suggested large, mobile vegetations on both the prosthetic aortic valve and native tricuspid valve. The presence of Staphylococcus epidermidis was revealed by multiple blood cultures. Surgery was not performed because of the history of aortic valve replacement one month ago. He developed acute right femoral artery thromboembolism, multiple cerebral infarction and splenic infarction during hospitalization and died of cerebral infarction after being discharged. This case underlines that patients with early PVE may have poor prognosis and fatal systemic embolism should be aware of in PVE patients with large vegetations present with dyskinesia, abdominal pain, and limb numbness. The timely echocardiography and vascular ultrasound are primary and reliable diagnostic methods in this scenario.